A Analisis Karakteristik Stomata Daun Rhoeo discolor (Adam Eva) Berdasarkan Waktu Pengambilan Sampel yang Berbeda - Al-hafidz, Nadia Nur Khamilah; Nasywa Liza Zahirah; Tiara Alifia Azzahra; Ratna Dewi Wulaningsih (Biosel Biology Science and Education, 2025)
Stomata are important structures in leaves that function in gas exchange and regulating air loss. The research focuses on the characteristics of Rhoeo discolor leaf stomata which are influenced by sampling time, taking into account environmental factors such as light, temperature and humidity. The aim of this research is to provide insight into the physiological adaptation of tropical plants to environmental change. The method used includes observing stomata in the morning (08.00 WIB) and afternoon (16.00 WIB) using a light microscope, where five samples are taken at each observation time to analyze the number of open and closed stomata. The results showed that the average number of open stomata was higher in the morning (24 stomata) than in the afternoon (17 stomata). This results in high stomata density in the morning, while in the afternoon it is low. Not only that, for the characteristics of stomata based on the location of the stomata on the leaf surface, the Rhoeo discolor stomata type is the Amphistomatic type. Meanwhile, based on its shape, the type of stomata that these stomata have is the tetracytic stomata type. In conclusion, sampling time has a significant effect on the characteristics of stomata in Rhoeo discolor, with more stomata opening in the morning associated with higher light intensity, supporting the efficiency of photosynthesis and air use in plants. Keywords: Stomata, Rhoeo discolor, Photosynthesis, Environmental Conditions